Potret Tata Kelola Ekonomi Hijau dalam Pembangunan Berkelanjutan di Indonesia Timur - Syamsul Bahri Abd. Rasyid; Misran; Herdin Arie Saputra (Jurnal Bina Praja, 2024)
Despite its potential benefits to humanity, the green economy fails to ensure an optimal balance and is instead a political concern. The global crisis includes climate disasters and is characterized by climate change, biodiversity loss, massive deforestation, administrative challenges, and other ecological damage. These exacerbate concerns for the environment, society, and economic balance. However, public understanding of green governance is lacking in Southeast Asia, which is considered a potential obstacle to public consensus on forest-dependent interests. Media coverage of forest governance is considered an important source of information in shaping public opinion as it generates digital representations. This study aims to investigate the presence of green economic governance in sustainable development in online news articles through content analysis of media coverage. Over two years (01/01/2020-01/01/2022), researchers collected Indonesian-language articles using the NCapture feature of NVivo 12 Plus, specifically focused on the topic "Environment." A total of 191 national and regional articles provided coverage. The result showed that the regional media Kabapulau.co.id dominates the level of reporting on green economy discourse in North Maluku, and the five online media are equally prominent regarding the natural resource efficiency index. This does not confirm that the environmental management carried out in North Maluku has adhered to the principles of green economy and sustainable development, considering that most of the news carried out by each media contradicts the indicators of green economy and sustainable development goals.